PENGAWASAN KEGIATAN PERPARKIRAN DI KOTA PEKANBARU TAHUN 2023 - Ardani, Cindy; Wasillah, Asiah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Parking is a crucial aspect of traffic management and urban mobility because it impacts safety, comfort, and smooth transportation. Parking management in Pekanbaru City is regulated by Regional Regulation Number 2 of 2009 concerning Traffic and Road Transportation, specifically Article 251, which regulates the obligations of parking attendants. However, in practice, parking attendants still fail to comply with these provisions. This study aims to describe the supervision of parking activities in Pekanbaru City in 2023. The research location is Binawidya District, using a qualitative descriptive approach. Data were obtained through interviews and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The study uses Syafri Sofyan's supervision theory, which consists of four indicators: expectation, allocation, monitoring performance, and corrective action. The research results show that parking supervision in Pekanbaru City is suboptimal. Based on the expectation indicator, some parking attendants have not complied with the attribute and ticket requirements. Regarding allocation, the number of personnel and supervision facilities are inadequate. Performance monitoring is ineffective due to low public awareness of complaints. Meanwhile, corrective action has not provided a deterrent effect, resulting in repeated violations. Strengthened supervision is needed to improve order and the quality of parking services in Pekanbaru City. Keywords: Supervision, Activities, Parking